A robust face recognition system - Pang, Ying Han; Ngo, David Chek Ling; Teoh, Andrew Ben Jin (Springer Berlin Heidelberg, 2005)
This paper proposes a robust face recognition system, by providing a strong discrimination power and cancelable mechanism to biometrics data. Fisher's Linear Discriminant uses pseudo Zemike moments to derive an enhanced feature subset. On the other hand, the revocation capability is formed by the combination of a tokenized pseudo-random data and the enhanced template. The inner product of these factors generates a user-specific binary code, face-Hash. This two-factor basis offers an extra protection layer against biometrics fabrication since face-Hash authenticator is replaceable via token replacement.